The Fallacy of Zero Inventories for Purchased Parts in Small Manufacturing and Job Shops - William E. Mueller; Gholam H. Massiha; Corinne Dupuy (Institute of Advanced Engineering and Science, 2015)
In this article we examine the soundness of receiving most vendor shipments just prior to the time of use and then immediately delivering them from the receiving area to the point of use by some small US manufacturing industry. This approach in theory would save handling cost, storage cost, and inventory holding cost, the real world offers numerous pitfalls, especially for smaller manufacturers and job shops.